THE PHENOMENON OF CANCEL CULTURE: GUS MIFTAH'S INSULT TOWARDS AN ICED TEA SELLER IN THE DIGITAL ERA - Rosalinda, Syakirah; Istiqomah (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the interaction and social impact of religious figures who become subjects of cancel culture, with a focus on how religious messages can strengthen support for humanity and social justice rather than triggering radicalism. Method: Using a qualitative research methodology, this study applies Social Identity Theory and Social Construction of Reality Theory, employing virtual ethnographic analysis to examine netizens' conversations, comments, and interactions across various social media platforms. Data was collected through participatory observation and content analysis of relevant online discussions. Results: The study reveals that cancel culture significantly impacts both the virtual and real-world perceptions of public figures. Netizen interactions in the digital era show how society enforces norms and shapes digital communication. Additionally, the study identifies patterns of netizen strategies in expressing opinions and their role in the social dynamics of cancel culture. Novelty: This research contributes to understanding the social impact of cancel culture on religious figures, offering insights into how online communities influence public perception and enforce social norms, with a focus on the broader implications for digital communication in the context of social justice.